Notas taxonômicas sobre os Brachiacanthini neotropicais (Coleoptera, Coccinellidae, Hyperaspinae) Taxonomical notes on neotropical Brachiacanthini (Coleoptera, Coccinellidae, Hyperaspinae) - Julianne Milléo; Lúcia M. de Almeida (Iheringia: Série Zoologia, 2007)
Brachiacantha Chevrolat in Dejean, 1837, Hinda Mulsant, 1850, Cyra Mulsant, 1850 e Tiphysa Mulsant, 1850 foram estudados e é fornecida uma chave para os gêneros. Cleothera loricata Mulsant, 1850 é designada espécie-tipo de Cyra. O lectótipo de Brachiacantha sellata é designado. Três novas combinações são feitas: Cyra loricata (Mulsant, 1850), Cyra scapulata (Mulsant, 1853) e Cyra turbata (Mulsant, 1850). Estão incluídas diagnoses e ilustrações dos caracteres. Brachiacantha Chevrolat in Dejean, 1837, Hinda Mulsant, 1850, Cyra Mulsant, 1850 and Tiphysa Mulsant, 1850 were studied, and a key to genera is added. Cleothera loricata Mulsant, 1850 is designated type species of Cyra. The lectotype of Brachiacantha sellata is designated. Three new combinations are proposed: Cyra loricata (Mulsant, 1850), Cyra scapulata (Mulsant, 1853) and Cyra turbata (Mulsant, 1850). Diagnosis and illustrations of characters are provided.